AGROBACTERIUM-MEDIATED TRANSFORMATION OF PANAX VIETNAMENSIS HA ET GRUSHV. - Nhut, Duong Tan; Huy, Nguyen Phuc; Huong, Trinh Thi; Luan, Vu Quoc; Hien, Vu Thi; Tung, Hoang Thanh; Cuong, Do Manh; Bich Phuong, Chu Thi; Ngoc, Pham Bich; Trong, Nguyen Dinh; Hung, Nguyen Khac; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2018)
In recent years, the Agrobacterium-mediated genetic transformation system has become the most useful method widely used for the introduction of foreign genes into plant cells followed by regeneration of genetically improved plants. Panax vietnamensis Ha et Grushv. is a highly valued medicinal plant native to Vietnam with limited area of distribution. This report illustrates the possibilities of biotechnology for genetic transformation aimed at establishing an effective production of secondary metabolites in P. vietnamensis. In the present investigation, 0.5 cm2 leaf blades, 1 cm long leaf petioles and 0.5 cm3 callus clusters were used for the hairy root induction. Results indicated that hairy roots were induced on P. vietnamensis callus clusters co-cultivated with Agrobacterium rhizogenes strain ATCC15834 at OD600 of 0.5 with an infection time of 20 min and a supplementation of 100 mM acetosyringone. PCR amplification of the DNA isolated from the resulting hairy roots was used to confirm the presence of rol genes. Compared to in vitro rhizome cultures, hairy root cultures appear to be potential for continuous production of valuable secondary metabolites with similar saponin profiles. The protocol described in this study is simple and rapid and therefore, can be used for large-scale experiments for the rapid production of valuable compounds.